PENGARUH KONSUMSI JANTUNG PISANG TERHADAP PRODUKSI ASI PADA IBU NIFAS - Ulva Noviana (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
Exclusive breastfeeding production is the result of breast stimulation by the prolactin hormone produced by the anterior pituitary gland. If the baby sucks, the Exclusive breastfeeding will be removed from the lactiferous sinuses. The purpose of this study is to analyze differences on Exclusive breastfeeding production after consuming the banana infloresence. The design used in this study is one group pretest posttest design, independent variable isbanana infloresence and the dependent variable isthe production of exclusive breastfeeding. Population in study were all postpartum mothers who breastfeed on the first child (primi gravidarum) in Gertenga village POSKESDES Septian Eka K ST,r.keb Karang penang subdistrict Sampang as much as 10, a sample of 10 respondents, taking sample technique uses simple random sampling.Data retrieval uses questionnaire sheet and a paired Sample test Rank statistical test with α (0.05). The results showed that all of them (100%) suffered from non-smooth breastfeeding preoductionbefore being given banana infloresence drink and after being given banana infloresence drink almost all (80%) breast milk was smooth. Based on the statistical test paired Sample test Rank test results obtained p value (0.002) <α (0.05) then Ha is accepted and H0 is rejected which means that there is a difference in exclusive breastfeeding production after consuming the banana infloresence. Suggestion for postpartum mothers who are breastfeeding who have not smooth exclusive breastfeeding production is to start getting used to consuming food or drinks that can facilitate the production of breastfeeding, one of them is the banana infloresence drink